Modelling kilonova afterglows: Effects of the thermal electron population and interaction with GRB outflows. Issue 2 (23rd January 2023) - Nedora, Vsevolod; Dietrich, Tim; Shibata, Masaru; Pohl, Martin; Crosato Menegazzi, Ludovica
Abstract: Given an increasing number of gamma-ray bursts accompanied by potential kilonovae, there is a growing importance to advance modelling of kilonova afterglows. In this work, we investigate how the presence of two electron populations that follow a Maxwellian (thermal) and a power-law (non-thermal) distribution affect kilonova afterglow light curves. We employ semi-analytic afterglow model, PyBlastAfterglow . We consider kilonova ejecta profiles from ab-initio numerical relativity binary neutron star merger simulations, targeted to GW170817. We do not perform model selection. We find that the emission from thermal electrons dominates at early times. If the interstellar medium density is high (${\simeq }0.1\, \, \text{cm}^{-3}$ ), it adds an early time peak to the light curve. As ejecta decelerates, the spectral and temporal indexes change in a characteristic way that, if observed, can be used to reconstruct the ejecta velocity distribution. For the low interstellar medium density, inferred for GRB 170817A, the emission from the non-thermal electron population generally dominates. We also assess how kilonova afterglow light curves change if the interstellar medium has been partially removed and pre-accelerated by laterally expanding gamma-ray burst ejecta. For the latter, we consider properties informed by observations of GRB170817A. We find that the main effect is the emission suppression at early time ${\lesssim }10^{3}\, $ days, and at its maximum it reaches ${\sim }40{{\ \rm per\ cent}}$ when the fast tail of the kilonova ejecta moves subsonically through the wake of laterally spreading gamma-ray burst ejecta. The subsequent rebrightening, when these ejecta break through and shocks form, is very mild (${\lesssim }10{{\ \rm per\ cent}}$ ) and may not be observable.